Peran Dinas Terkait dalam Pemanfaatan Teknologi Informasi di Desa Temayang Kecamatan Temayang Kabupaten Bojonegoro - Nagara, Yudha Surya; Yuliati, Yayuk; Toyba, Heri (Universitas Batanghari Jambi, 2024)
The aim of this research is to analyze the role of the Agriculture Service in supporting the use of information technology in the community in Temayang Village, Temayang District, Bojonegoro Regency. This research uses a qualitative approach with descriptive analysis. Determining informants was carried out using the snowball method. Data collection techniques using interviews, observation and document analysis. Meanwhile, data analysis techniques use data reduction, data presentation and drawing conclusions and verification. The research results show that Temayang Village, Temayang District, Bojonegoro Regency has experienced a significant increase in access to information technology infrastructure with a stable internet network, public Wi-Fi, and three towers. Farmers' digital literacy is also good, with the use of smartphones for communication and internet access related to agriculture. The Department of Agriculture plays an important role in providing counseling and training, increasing the use of information technology by village communities.